(untitled) (Scientific journal of the Fergana State University, 2023)
Interaction in society involves interaction between people that might be identified as intercultural communication. Spontaneous communication where speakers might be of various intercultural origin the interaction has to be flexible in language skills i.e. take into account the language ,thinking, traditions , intellection and beliefs. Modern learning and teaching a language suggests concentration not only on language acquisition, accuracy and fluency as well as the massage sent by each member of the conversation ,i.e. the cultural origin of co-speakers. Using a technology of working with video tasks in the classroom is one of the beneficial approaches to develop communicative skills in EFL learners.